Mechanisms of regulation electric and contractile activity smooth muscle cells: the role of cytoskeleton - M. A. Medvedev; M. B. Baskakov; S. V. Gusakova; I. V. Kovalyov; O. S. Melnik; V. V. Popov; L. V. Kapilevich (Бюллетень сибирской медицины)
The influence of modulation of cytoskeleton by colchicine, vinblastine, cytochalasine B and docetaxel on contractile reactions of smooth muscle cells caused by electric stimulus, depolarization, phenylephrine has been investigated by the mechanographical method, by the methods of the double sucrose gup junction. It is established, that induced by a isoosmotic hyperpotassium solution of reduction of smooth muscle of the rat’s aorta, and also caused depolarization stimulus potentials of action and reductions smooth muscle cells from guinea pig urethra, depend more on the condition of microfilaments cytoskeleton than on microtubules. The reduction of smooth muscles cells of an aorta of the rat, caused by isoosmotic striction, is suppressed under the destruction microfilaments whereas the reduction in a hyperosmotic solution depends on a condition of both microfilaments, and microtubules. Cytoskeleton’s microfilaments of aorta’s smooth muscles and microtubules of smooth muscles of cells ureter are involved in mechanisms of action phenylephrine’s action on contractile activity of smooth muscle cells of an aorta and ureter.